Analisis Bentuk Struktur Sosial dalam Kisah Layālī Turkistān Karya Najīb Al-Kailānī - Hasfikin S; Ainy Khairun Nisa; Nuz Chairul Mugrib (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2022)
This research is analysis of social structure in Layali Turkistan Novel written by Najib Al-Kailani aims to reveal the social structure in the story. This research is qualitative research. It uses literature research or library research and research method is content-analysis or descriptive qualitative. The approach used in this research is emic approach including literature, sociology and history socio. Type of social structure portrayed in the story in Layali Turkistan Novel written by Najib Al-Kailani is social status and role. Social status or social class in this story is ascribed status, achieved status and assigned status. Whereas, social role involving norms which are related with position or status to someone in society is the concept about what person is able to be achieved in society as social community and individual behavior which is important to social structure of society.